2004
DOI: 10.4012/dmj.23.67
|View full text |Cite
|
Sign up to set email alerts
|

Mechanical Evaluation of Effect of Grape Seed Proanthocyanidins Extract on Debilitated Mandibles in Rats

Abstract: Grape seed proanthocyanidins extract (GSPE), whose principal ingredient is proanthocyanidins, shows many activities such as cholesterol lowering effects, antioxidant effects, anti-tumor effects, cardioprotective effects, and protection against ultraviolet rays. However, reports of the effects of GSPE on bone are rare. We performed a mechanical analysis of the effect of GSPE on the interior structure of rat mandibular bone in the growth period, using three-dimensional peripheral quantitative computed tomography… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
15
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 44 publications
0
15
0
Order By: Relevance
“…, Gunjima et al . , Kojima et al . ) and irreversible pulpal damage (Alani & Toh , van Dijken et al .…”
Section: Introductionmentioning
confidence: 95%
See 1 more Smart Citation
“…, Gunjima et al . , Kojima et al . ) and irreversible pulpal damage (Alani & Toh , van Dijken et al .…”
Section: Introductionmentioning
confidence: 95%
“…Restorative Dentistry with resin composites and adhesive systems has evolved, adhesive stability to dentine is challenging, as it fails to provide longevity for both restorative materials and maintenance of pulp health (Perdigão et al 2013, Sabatini & Pashley 2014. The characteristics of dentine, such as the gradient of moisture and tubular structure (Perdigao 2010), polymer components and leaching of monomers (Hashimoto et al 2003), hydrolytic and enzymatic degradation (Toledano et al 2010, Carrilho 2012 and other factors in cascade can compromise the stability of the hybrid layer, resulting in staining at restoration margins (Corder et al 2004, Gunjima et al 2004) and irreversible pulpal damage (Alani & Toh 1997, van Dijken et al 2007) in the long term.…”
Section: Introductionmentioning
confidence: 99%
“…There are few reports on using bisphosphonate as a treatment for steroid‐induced osteoporosis in childhood (Cimaz, 2002; Srivastava and Alon, 2003). In the oral field, although the use of grape seed proanthocyanidins for the treatment of osteoporosis (Gunjima et al , 2004; Kamitani et al , 2004; Kojima et al , 2004; Ishikawa et al , 2005) and the relation between decreased maxillary bone mineral content and loss of teeth in osteoporosis (Krall et al , 1996; Gilles et al , 1997; Jeffcoat, 1998) have been reported, so far there is no study for the effect of bisphosphonate on the jawbone in steroid‐induced osteoporosis during childhood.…”
Section: Introductionmentioning
confidence: 99%
“…In a study, which scrutinized the effect of GSE on mandible, it was demonstrated that rats fed with standard feed combined with GSE had higher mandibular cortical bone density, cortical and trabecular bone mineral content, in addition to increased mechanical bone properties such as formation, quality and endurance (42,43). These limited number of studies showed that GSE was quite active on bone tissue.The findings of the present study also demonstrated that GSE was quite effective on mandibular defect induced rat liver as a result of the applied dose and period and displayed protective antioxidant action in liver tissue against the oxidative damage that could occur during bone recovery process.…”
Section: Discussionmentioning
confidence: 99%